Challenges experienced by cancer patients receiving treatment at Oshakati oncology clinic, Oshana region, Namibia - Mulenga, Ester; Mutanga, Elise (International Journal of Advanced Nursing Studies, 2021)
People living with cancer encounter different problems; some are related to their diagnoses and treatment. The purpose of the study was to explore and describe the challenges experienced by cancer patients receiving treatment at Oshakati oncology clinic in Namibia. A qualitative, exploratory and descriptive study was conducted using purposive sampling and twelve patients diagnosed with different types of cancer were interviewed using unstructured individual in-depth interview. Data were transcribed verbatim and Tesch `s method was used to analyze the data.The study revealed multifaceted challenges which include physical constraints such as physical ailments, long distance to health facilities and excessive travelling; financial and resource constraints as well as other challenges such as negative attitudes of health workers, poor communication and inadequate provision of information to patients. The study concluded that understanding those challenges will assist the government, private sectors, non- governmental organization and health workers to come up with intervention strategies to support cancer patients effectively. The study recommends the need to decentralize oncology services and to provide in-service training to the health workers working with patients living with cancer.Â Â